Antropoestética da memória: dimensões e expressões da signogravura como elemento do imaginário - Silva, Josualdo de Meneses (2013)
This research aims to study the characterization of (antropo) aesthetics memory as new design discursive theoretical-methodological in environmental sciences. This is basic research or fundamental theoretical elements of which will be arranged to help systematize concise and rigorous studies to substantiate the relationships that emerge between imaginary appropriation of nature, environment, signs and engraving on rock records. Consider will be analysis of the dimensions and aesthetic expressions associated with signogravura as part of the imaginary, through Itacoatiaras do Boi Branco - Pernambuco, basing themselves, especially in the theory anthropological and sociological of Gilbert Durand. A theoretical approach to the subject is marked by the interdisciplinary nature of research, sedimented in the inspiration of etnopesquisa crítica e multirreferencial. The research methodology is part of the interpretative paradigm / qualitative and exploratory method within the type of fundamental research and evidence base. The main instruments used in collecting information is the field journal, photography, documentary analysis and bibliographic sources available on the subject. The initial results of this research indicate the characterization of antropoestética and its relations with the imaginary consolidates the imagery and expressiveness signic contained, expressed and condensed by Itacoatiaras Boi Branco. Accordingly, the initial results give rise to processes-hermeneutic products formed by the assembling of primary and secondary sources, documents and pictures, which explain the relevance of integrative analyzes, convergent and natural, through which dialogue between different fields of knowledge, methods and theories antropoestética elucidate the power of memory in their movements constitution. This is social and scientific relevance both to the field of environmental science by its nature interdisciplinary, multifaceted and critical object in which this research contributes to overcoming simplistic and monolithic systematization about expressions and dimensions of signogravura in their relations with the environment and prehistoric cultures, and for the consolidation of future research on the national scene of historical archeology and environmental history, keeping them away from a predominant vision or qualitative or quantitative. Finally, the results point to the possibility of emerging interdisciplinarity, by interdisciplinarity, interdisciplinarity with the attitude interdisciplinary dialogue with traditions from the past that is updated by the creative power of imagination, nature and memory.